The association of religiosity with suicidal ideation and suicide attempts in the United Kingdom. (17th October 2018) - Jacob, L.; Haro, J. M.; Koyanagi, A.
Abstract : Objective: The goal was to analyze the association of religiosity with suicidal ideation and suicide attempts in a UK nationally representative sample. Methods: This study used cross‐sectional data from 7403 people who participated in the 2007 Adult Psychiatric Morbidity Survey (APMS). Religion was assessed with the question 'Do you have a specific religion?' with 'yes' and 'no' answer options. Lifetime and past 12‐month suicidal ideation and suicide attempts were assessed. The association between religiosity and suicidality was studied in multivariable logistic regression models adjusted for sociodemographic, behavioural, and psychopathological factors. Results: Compared to those without a religion, the prevalence of past 12‐month suicidal ideation (3.2% vs. 5.4%), past 12‐month suicide attempts (0.4% vs. 0.9%), lifetime suicidal ideation (11.2% vs. 16.4%), and lifetime suicide attempts (3.6% vs. 6.0%) was lower among those with a religion. In the fully adjusted model, having a religion was significantly associated with lower odds for all types of suicidality except past 12‐month suicide attempts: suicidal ideation (past 12‐month: OR = 0.71, 95% CI = 0.51–0.99; lifetime: OR = 0.83, 95% CI = 0.69–0.99) and suicide attempts (past 12‐month: OR = 0.71, 95% CI = 0.35–1.45; lifetime: OR = 0.69, 95% CI = 0.53–0.90). Conclusion: There is a negative association between religiosity and suicidality in the UK. Future studies should focus on the underlying mechanisms.